2018
DOI: 10.1037/cou0000247
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the Psychology of Working Theory with racially and ethnically diverse employed adults.

Abstract: The present study tested key tenets of the Psychology of Working Theory (PWT) in a sample of 526 racially and ethnically diverse employed adults. The authors investigated how economic resources and marginalization predicted decent work through experiences of work volition and career adaptability. Support for the hypotheses was mixed. There was a direct, negative relation between marginalization and decent work; a direct, positive relation between economic resources and work volition; and a direct, negative rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
145
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(166 citation statements)
references
References 70 publications
18
145
1
2
Order By: Relevance
“…Those who have the capacity to make their own career-related decisions tend to have positive decent work opinions. The majority of studies support this assumption empirically [9,10,56]. Therefore, the study advanced the fifth hypothesis: Hypothesis 5 (H5).…”
Section: Hypothesis 3 (H3) Work Volition Positively Influences Careementioning
confidence: 78%
See 2 more Smart Citations
“…Those who have the capacity to make their own career-related decisions tend to have positive decent work opinions. The majority of studies support this assumption empirically [9,10,56]. Therefore, the study advanced the fifth hypothesis: Hypothesis 5 (H5).…”
Section: Hypothesis 3 (H3) Work Volition Positively Influences Careementioning
confidence: 78%
“…Decent work plays a central role in the model, and it has five components: safe working conditions, access to health care, sufficient compensation, free time and rest during the work week, and values match between working place and family [8]. Previous studies have tested the model in various countries, such as Brazil [17], South Korea [18], Switzerland [19], UK [20], Italy [21], Turkey [22], Portugal [23], and China [9], and in various sorts of respondents, such as low-income employees [24], people who suffer from Chiari malformation [25], racially and ethnically diverse employees [10], and emerging adults [11].…”
Section: Psychology Of Working Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Douglas et al found no direct effect of career adaptability on decent work. Other research has affirmed a predictive relations between marginalization and decent work and, indirectly via work volition, in an ethnically-diverse American sample; however, again, there was no predictive relation with career adaptability (Duffy et al, 2018). Career adaptability has, nonetheless, been found to predict decent work in other samples (e.g., Tokar & Kaut, 2018).…”
Section: The Psychology Of Working Theory and Decent Workmentioning
confidence: 90%
“…Research has begun to build substantive empirical evidence for the utility of PWT (e.g., Autin, Duffy, Jacobson, Dosani, & Bott, 2018;Douglass, Velez, Conlin, Duffy, & England, 2017;Duffy et al, 2018;Kossen & McIlveen, 2018;Tokar & Kaut, 2018). Additionally, PWT tenets rest on a foundation of previous empirical work linking contextual variables, work volition, career adaptability, and well-being (e.g., Duffy et al, 2012;Zacher, 2014).…”
Section: Psychology Of Working: a Transformative Theorymentioning
confidence: 99%